2009
DOI: 10.1088/0022-3727/42/16/165503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma aerodynamic actuation on oblique shock wave in a cold supersonic flow

Abstract: Wedge oblique shock wave control using an arc discharge plasma aerodynamic actuator was investigated both experimentally and theoretically. Schlieren photography measurements in a small-scale short-duration supersonic wind tunnel indicated that the shock wave angle decreased and its start point shifted upstream with the plasma aerodynamic actuation. Also the shock wave intensity weakened, as shown by the decrease in the gas static pressure ratio of flow downstream and upstream of the shock wave. Moreover, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…The other mechanism is the generation of streamwise vortices caused by the pulsed arc discharges, which leads to a fuller boundary layer profile, making it less resistant to separation. Wang et al 15 employed a pulsed-arc discharge in the presence of an external magnetic field to weaken the separation shock generated by a 20 • compression ramp placed in a Mach 2.1 flow. The authors reported an increase in the weakening of the shock strength with external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The other mechanism is the generation of streamwise vortices caused by the pulsed arc discharges, which leads to a fuller boundary layer profile, making it less resistant to separation. Wang et al 15 employed a pulsed-arc discharge in the presence of an external magnetic field to weaken the separation shock generated by a 20 • compression ramp placed in a Mach 2.1 flow. The authors reported an increase in the weakening of the shock strength with external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…直流放电等离子体较强的加热效应, 可以产生 较高的等离子体密度. 当施加合适的外部磁场时, 通 过 磁 流 体 动 力 的 约 束 作 用 , 可 以 降 低 放 电 功 率 需 求 [132] , 同时提高等离子体控制效果 [133] . 火花放电等离子体激励器的工作特性受能量沉 积大小、激励器腔体和出口大小的影响 [136,137] , 另外 Belinger 等人 [138] 还实验研究了电能的释放速率对激 励器工作特性的影响.…”
Section: 脉冲射流激励器unclassified
“…Yan [8] promoted the supersonic boundary layer transition using the so-called 'thermal bump' (∆Tw=500K, f=100 kHz) through vortical structures. Falempin and Wang [9][10] investigated the control authority of the steady DCD (2-10 kW and 1-1.5 kW) on shock wave modification. It was found that the resulted thermal choking could weaken the shock wave strength and reduce the shock drag.…”
Section: Introductionmentioning
confidence: 99%